2005
DOI: 10.1007/s10535-005-7015-6
|View full text |Cite
|
Sign up to set email alerts
|

High irradiance can minimize the negative effect of exogenous sucrose on the photosynthetic capacity of in vitro grown coconut plantlets

Abstract: There is increasing evidence that the sucrose normally added to the culture medium affects negatively the photosynthetic capacity of plantlets. At the same time, however, sucrose cannot be eliminated from the medium, as it is required for normal in vitro growth. We argue that this is true only under the conventional light conditions of growth-rooms. In the present paper irradiance of growth-rooms was increased 10 times and although the sucrose-inhibitory effect was found at high sucrose concentrations, it was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…However, the addition of sucrose to the root medium further enhanced root and shoot growth. These observations support previous studies that showed enhancement of growth by sucrose under photomixotrophic conditions (Cournac et al 1991, Paul and Stitt 1993, Furbank et al 1997, Tichá et al 1998, Fuentes et al 2005. In those studies, the increase in biomass in response to exogenous sucrose occurred mainly under low irradiance and low CO 2 (Cournac et al 1991, Tichá et al 1998, Le et al 2001.…”
Section: Discussionsupporting
confidence: 87%
“…However, the addition of sucrose to the root medium further enhanced root and shoot growth. These observations support previous studies that showed enhancement of growth by sucrose under photomixotrophic conditions (Cournac et al 1991, Paul and Stitt 1993, Furbank et al 1997, Tichá et al 1998, Fuentes et al 2005. In those studies, the increase in biomass in response to exogenous sucrose occurred mainly under low irradiance and low CO 2 (Cournac et al 1991, Tichá et al 1998, Le et al 2001.…”
Section: Discussionsupporting
confidence: 87%
“…However, an initial high sugar content in the medium can impair the carboxylation rate of explants (Langford and Wainwright 1987;Cournac et al 1991) and have negative effects on the plants that may be related to increased plant susceptibility to feedback inhibition because of an excess of carbohydrates stored in the leaves and low sugar exporta- (Capellades et al 1991;Fuentes et al 2005a). This in turn induces the loss of photosynthetic activity (Xu et al 1994;Arigita et al 2002;Fuentes et al 2005b), the decrease in the amount of rubisco and its carboxilation efficiency (Fuentes et al 2005b) or even structural disorders (Dimassi-Theriou and Bosabalidis 1997).…”
Section: Discussionmentioning
confidence: 99%
“…These two techniques applied to coconut could possibly facilitate the rapid multiplication of robust plantlets, thereby creating a platform for mass clonal propagation. However, the ex vitro acclimatization of somatic embryo-derived plantlets has yet to be refined, with present rates of success of around 50 % so far (Fuentes et al 2005a). Further improvements may come from using a photoautotrophic culture system and/or through the incorporation of fatty acids, notably lauric acid, into the plantlet maturation medium (López-Villalobos et al 2001.…”
Section: Clonal Propagation Via Somatic Embryogenesis Somatic Embryogmentioning
confidence: 99%